Kitab Tajwid Nazm Batu Ngompal Tuan Guru Kyai Haji Muhammad Zainuddin Abdul Madjid - Salim Rahmatullah; Mohd. Shafiee Bin Hamzah (Sekolah Tinggi Agama Islam Sadra, 2022)
Many Scholars in the archipelago have done the teaching of Quranic sciencies, for example tajwid science. One of them is Maulana Sheikh Tuan Guru Kiai Hajj Muhammad Zainuddin Abdul Madjid. This charismatic scholar who is from Lombok, Nusa Tenggara Barat has the book under the title, Nazam Batu Ngompal. However, this book is not as popular as the books of other scholars in Indonesia. Thus, this article tries to describe and see the superior or unique side, and the shortcomings, as a form of popularization in the archipelago. This article is a qualitative article that uses the interview method and literature review in collecting data, which is then analyzed and described. As a result, there are five unique features of Nazam Batu Ngompal: First, the uniqueness of the name, which is different from the Nusantara books in general. Second, it is written in three languages: Arabic, Indonesian, and Sasak. Third, written using Arabic-Jawi or Arabic-Pegon script. Fourth, the dominant language is Indonesian but arranged according to Arudh Science. Fifth, it contains messages about the importance of recitation and learning from the experts. Meanwhile, the drawback is that there is a need for a broad consultation.